Relationship between RALE Score, Age, Gender, D-Dimer, Diabetes Mellitus and Hypertension with Mortality Rate of COVID-19 Patients in the Intensive Care Unit - Ferdion, Ivan; Widiastuti, Widiastuti; Subagio, Yusup; Wujoso, Hari (Smart Medical Journal, 2022)
Introduction: The evaluation of changes in RALE scores on chest radiography and increased D-Dimer values of COVID-19 patients can be prognosticators of severity in the progressive phase and risk of ARDS. This study aims to determine the relationship between Rale scores and mortality of COVID-19 patients in the Intensive Care Unit (ICU) at RSUD Dr. Moewardi.Methods: This research is an analytical observational study with a cross sectional approach was conducted on COVID-19 patients who had undergone a chest radiography and a D-Dimer examination at RSUD Dr. Moewardi in the period May 2021 to July 2021.Results: This research included of 126 patients with 109 (87%) have died and 17 (13%) lived. Increased RALE and D-Dimer scores were associated with mortality of COVID-19 patients in the ICU while gender (p=0.416), age (p=0.336), diabetes mellitus (DM) (p=0.852), and hypertension (p=0.464) did not have a significant relationship with the outcome of COVID-19 patients admitted to the ICU with p>0.05. The RALE score has an OR = 7.566 (95% CI = 2.117-27.043) which means that the increase in the RALE score is 7.566 times greater for the death outcome than the RALE score which remains or decreases. The D-Dimer got an OR value of 3,679 (95% CI=1.169-11,576) which means that D-Dimer >2000 has a 3.655 times greater risk of death than D-Dimer <2000 in COVID-19 patients treated in the ICU.Conclusion: There is a relationship between changes in RALE and D-Dimer scores with the mortality rate of COVID-19 patients in the ICU of RSUD Dr. Moewardi. Future research is expected to analyze other factors that have the potential to bias the results of the study such as changes in D-Dimer values, sociodemographic factors, clinical conditions and medical history in research subjects.